Key environmental factors underlying terrestrial arthropod abundance and diversity in alley-cropping and monoculture oil palm plantations - Ashraf, Mohamad; Hosaka, Tetsuro; Norhisham, Ahmad R.; Sanusi, Ruzana; Tohiran, Kamil A.; Zulkifli, Raja; Azhar, Badrul (The Japan Society of Tropical Ecology, 2023)
Oil palms are extensively planted in tropical countries and causing a severe decline in biodiversity. Alley-cropping is an agroforestry practice that has been proven to sustain greater diversity of terrestrial arthropods than monoculture plantations. However, the environmental factors responsible for these differences remain unclear. This study aimed to identify the environmental factors influencing terrestrial arthropod abundance and richness in alley-cropping and monoculture oil palm plantations. We sampled terrestrial arthropod using 840 pitfall traps under seven treatments: oil palm alley-cropping systems with Bactris, bamboo, black pepper, cacao, and pineapple; and two oil palm monoculture systems. We assessed the microenvironment (presence/absence of alley cropping, vegetation coverage, soil surface temperature, soil moisture, light intensity, and relative air humidity) at each sampling site. Overall, 14,358 arthropods belonging to 19 orders were collected. The presence of alley-cropping was the only factor that positively affected the arthropod abundance and order richness. Arthropod abundance was negatively affected by soil moisture, suggesting that the dominant species, even in alley-cropping, were generalist species acclimated to dry soil conditions. Our study suggests that alley-cropping in oil palm plantations could increase the terrestrial arthropods diversity by increasing the diversity of vegetation (even with only one additional crop), rather than improving habitat microclimate. However, as microclimate remained intense, alley-cropping with only one secondary crop in our study site would not be sufficient to conserve forest specialist species. We suggest that producers of oil palm pay close attention to the potential of alley-cropping incorporating multiple secondary crops to increase biodiversity in plantations.